ECOLOGICAL AND HYGIENIC CONCEPT OF PRESERVATION OF SIVERSKIY DONETS RIVER UPPER REACHES AS IMPORTANT CONTRIBUTION TO TRANSBOUNDARY POLITICS OF WATER RESOURCES MANAGEMENT IN UKRAINE - Shcherban, N.G.; Shevchenko, E.A.; Savchenko, V.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
System analysis and assessment of administrative and legislative acts of Ukraine regarding problems of use and preservation of transboundary resources were performed in the view of recommendations of UN General Assembly and European Union. Long-term complex specific ecological and hygienic studies were done for assessment of anthropogenic effect on upper reaches of Siverskiy Donets river within Belgorod and Kharkiv regions. Ecological and hygienic concepts of sanitary preservations of Siverskiy Donets river was developed as a basis for optimization of water supply of the regions in Ukraine and Russia within the basin of Siverskiy Donets river.